Crosstalk Between Histamine and T Cells in Allergic Diseases - Saeki, Mayumi; Nishimura, Tomoe; Kaminuma, Osamu; Ohtsu, Hiroshi; Mori, Akio; Hiroi, Takachika (Current Immunology Reviews (Discontinued), 2016)
Histamine, a prominent mediator of the symptoms and pathogenesis of allergic diseases, is produced not only by mast cells and basophils via the classical degranulation process but also by other immune cells including T cells via a neosynthesis process. Interestingly, T cells produce and are affected by histamine. Various T cell functions are also regulated by histamine via H1, H2, and H4 receptors. We recently demonstrated that T cells induce massive allergic inflammation without assistance from the immunoglobulin E (IgE)/mast cell-dependent pathway, and histamine may be involved in the development of allergic diseases via the functional modulation of and production by T cells. Based on these reports, we propose a new role of histamine and T cells in allergic diseases that differs from the established paradigm. Aside from our recent study showing the downregulation of regulatory T (Treg) cells by histamine via H1R and H4R in a murine allergic dermatitis model, the detailed roles of histamine and T cells in histamine production, expression of histamine receptors, and histamine-mediated activity for a series of T cell subsets remain to be elucidated.
Keywords: T cells